The search for interreligious convivance, ongoing challenge and charge - Gort, Jerald D. (Verbum et ecclesia, 2008)
This essay deals with the relationship between Christianity and other religions. Part one looks briefly at the matter of religion itself. Part two provides a condensed historical survey of the attitude of Christianity toward the world outside itself: the approach of the church to other religions changed from initial appreciation through a long phase of rejection to an increasingly affirmative posture in recent times. This shift is explained by a number of causal factors that gave rise to new understandings regarding God’s work in the world and Christian mission, which in turn led to the emergence of various theologies of religion. The question confronting religious people today is how to foster the removal of interhuman divisions and the promotion of justice and peace. One potential means of achieving this goal is interreligious dialogue. In part three, the author delineates his concept of the four facets of dialogue: that of histories, of theologies, of spiritualities, and of life. Dialogue at all four of these levels is key to the establishment of interreligious convivance, which in our present world is prerequisite to the security and well-being of humanity.